Arthropod phytophages complexes on the territory of the republican landscape reserve «Ozery» (Grodno Region, Belarus) - Rhyzhaya, Aleksandra V.; Hliakouskaya, Katsiaryna I. (Experimental Biology and Biotechnology, 2023)
The state and functioning of native and invasive species of phytophages communities that damage trees and shrubs in specially protected natural areas of the Grodno-Predpolessky region were established. In the field season of 2021, representatives of 2 classes of arthropods have been identified on the territory of the republican landscape reserve «Ozery» – the class Arachnida and the class Insecta Ectognatha. In total, 85 species of phytophages from 54 genera, 19 families and 6 orders (Prostigmata, Coleoptera, Diptera, Hemiptera, Hymenoptera and Lepidoptera) were found. The largest number of species (29 species, or 34 % of their total number) belongs to the order Lepidoptera. The vast majority of registered arthropod phytophages (18 species from 14 genera, 9 families and 4 orders) use English oak (Quercus robur L., 1753) as a food plant. In total, 11 invasive species was noted in the surveyed sample plots. The largest number of invasive phytophages is trophically associated with black locust (Robinia pseudoacacia L., 1753). The data obtained to identify threats from the introduction of invasive species into native communities can be used.